Odpowiedzi

2010-01-11T17:11:17+01:00
H=a√3/2 czyli:

a) √3

√3=a√3/2 |*2
2√3=a√3 |:√3
a=2

b)h=√12

√12=a√3/2 |*2
2√12=a√3 |:√3
a= 2√12/√3 * √3/√3
a= 2√36/3
a= 12/3
a=4

c) h=√6

√6=a√3/2 |2
2√6=a√3 |:√3
a=2√6/√3 * √3/√3
a=2√18/3
a=2*3√2/3
a=6√2/3
a=2√2

d) h=√1,5

√1,5=a√3/2 |*2
2√1,5=a√3 |:√3
a=2√1,5/√3 *√3/√3
a=2√4,5/3
a= 2*3√0,5/3
a=2√0,5
2 5 2
2010-01-11T17:13:46+01:00
H=a√3/2 /*2
2h=a√3 /:√3
2h/√3=a

a)√3 cm

2*√3
________=a
√3

2√3 √3
_______*___=a
√3 √3

2*3
____=a
3

a=2cm

b)√12 cm

2*√12
______=a
√3

2√12 √3
_____* ___=a
√3 √3

2*6
___=a
3

a=4cm


c)√6 cm

2*√6
______=a
√3

2√6 √3
_____* ___=a
√3 √3

2√18
______=a
3
2*√9*2
______=a
3

6√2
______=a
3

a=2√2 cm

d)√1,5 cm

2*√1,5
________=a
√3

2√1,5 √3
_______*___=a
√3 √3

2*√4,5
______=a
3

2*√2*2,25
_________=a
3

2*1,5√2
_______=a
3

a=√2cm
2 5 2